Effect of Turmeric (Curcuma longa) Supplementation on Growth, Antioxidants and Immunity of Broilers - Sethy, Kamdev (Indian Journal of Animal Nutrition, 2021)
To assess the effect of turmeric (Curcuma longa) supplementation on growth, antioxidants and immunity of broiler chickens, one hundred twenty day-old Vencobb broiler chicks were randomly distributed into three dietary treatments with four replicates containing 10 chicks each. Group I served as control (without any supplementation), whereas birds in groups II and III were supplemented with 0.5% and 1.0% Curcuma longa powder respectively and the trial was lasted for 5 weeks. Body weight was measured at the end of each week, whereas blood samples were collected at the end of the experiment to study the antioxidant enzymes status and immunity of birds. The results indicated that addition of Curcuma longa powder caused significant (P